PERANCANGAN TEMPAT SAMPAH OTOMATIS BERBASIS MIKROKONTROLER ARDUINO DAN GSM SIM 900 - ASDI SUYONO; MUNNIK HARYANTI (JURNAL TEKNIK INDUSTRI, 2018)
Processing of garbage that is not well integrated, leading to a lack of interest in the community for disposing of waste in place. The impact caused could interfere with health and hygiene environment. The methods used in this research is the design tool, with stages of the needs analysis, designing and field circuit, Making Tools, testing and analysis tools. The result of the design is a Microcontroller Based Automatic trash can which is composed by the ultrasonic sensor, PIR sensor (Infrared Pasive), ISD 1760 sound Player module, lcd screen and GSM sim 900. There are different concepts of automated trash on this one, other than can open automatically and issue a unique sound, the bin is equipped with a gsm sim 900 module that is used to send sms messages, this message is sent to a janitor when the capacity of the bin is full. Automatic trash can has two main systems are the first arrival of the automatic detection, the sensor range up to 8 metres with a maximum angle of 90 degrees, with a detection range 0.5 seconds – 1.7 seconds. Both the Detection capacity of Automatic trash can, trash can full of garbage collection if the stated approach ≤ 10 cm. sensor trash can is devoted to a dry solid waste. With a variety of features that exist on this automatic trash can, it is hoped to grow interest in the community to dispose of trash in its place and the creation of a clean and healthy environment.Keywords: GSM sim 900, microcontroller Arduino, Automatic trash can, Ultrasonic Sensor, PIR Sensors.